The Conceptualization and Translation of Building Metaphors in Politics: A Comparative Study between Arabic and English - Arrdaini, Khuzami Muflih; Almaani, Bashar Osama (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aims to investigate how metaphors related to the domain of ‘building’ are used in political discourse. The study also seeks to identify linguistic and conceptual metaphors, their use, and their effects, as well as analyze the approaches involved in translating metaphors Methods: The methodology draws on a combination of conceptual metaphor theory (Lakoff & Johnson, 1980), and translation theories proposed by Newmark (1988) and Schäffner (2004). The data of this research is a selection of speeches delivered by Abdullah II, king of Jordan and former President Trump. Results: The study revealed that the metaphorical domain ‘building’ is widely used in politics, as metaphors from this domain are an effective tool for politicians to convey their viewpoints on a variety of political issues and complex policy positions. Such metaphors aim to depict goals as shared responsibilities; they also emphasize the need for cooperation between political leaders and the public. Conclusions: Metaphors are powerful linguistic tools in politics, which is why many political figures frequently rely on them. Furthermore, it has been argued that despite the differences between the two languages, they both use ‘building’ metaphors similarly.